Neuroleptic malignant syndrome in a general hospital - Valdivieso-Jimenez, Glauco (2022)
We describe the clinical presentation and diagnostic difficulties of a case of Neuroleptic Malignant Syndrome in a general hospital. The patient was an 18-year-old male with severe mental retardation and a history of seizures who received irregular treatment with risperidone and phenytoin. After presenting irritability, aggressiveness, and psychomotor agitation, he went to a psychiatric hospital where received an increase in the dose of risperidone. Subsequently, due to persistence of aggressiveness, he went to a psychiatric hospital where haloperidol, midazolam and levomepromazine were indicated, after few days developed oromandibular dystonia, temperature rise and generalized dystonia with difficulty swallowing food, which is why he went to hospital general and was diagnosed with Neuroleptic Malignant Syndrome. Patient received treatment with bromocriptine and diazepam during hospitalization with favorable evolution of neuropsychiatric symptoms. Neuroleptic Malignant Syndrome is a rare and fatal adverse event. It is associated with the use of psychotropics, especially antipsychotics.